PLINTH FROM THE TEMPLE IN HYENOS: THE RESULTS OF TEST STUDIES USING THE METHOD OF A.A. BOBRINSKY AND X-RAY PHASE ANALYSIS - Trebeleva, Galina Viktorovna; Klemesova, Marina Evgen'evna; Skakova, Izabella Vladimirovna; Dzopua, Arkadij Ivanovic (History, Archeology and Ethnography of the Caucasus, 2024)
The variety of plinths in the masonry of one monument marks the different stages of its construction or repair during operation, since they were produced by different teams and in different workshops. This article is devoted to the study of the ceramic tradition of making the composition of the original plastic raw materials and molding compounds. The study of the plinths was carried out using a method already proven at other monuments in Eastern Abkhazia: a comprehensive study using the method of A.A. Bobrinsky and X-ray phase analysis. Fragments of plinths for research were taken from two different areas: the Eastern and Western excavations. During the study, it was possible to establish that there are three traditions of preparing molding compounds, which are unevenly represented. Further, the traditions of preparing molding masses for bricks from temple in Gienos were compared with previously studied bricks from the temple in the Markul settlement. Both significant differences and similarities were identified in the manufacturing methods and traditions used. We can confidently speak about the manufacture of plinths for these two monuments, located close to each other, at a distance of 10 km, in two different places. This gives strong grounds for the conclusion that the production of plinths was located directly next to the construction site. The second conclusion: the relationship between individual traditions and the chronological stages of the temple’s existence is still preliminary. A study of the composition of plinths showed the promise of the research and will be continued.